The effects of Workplace violence on healthcare workers in Tunisia - M. Mnif; N. Smaoui; R. Feki; I. Gassara; S. Omri; M. Maalej; N. Charfi; J. Ben Thabet; L. Zouari; M. Maalej (European Psychiatry, 2022)
Introduction Exposure to violence affects employees and has implications for the quality of care provided.